2015
DOI: 10.1111/ppa.12385
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, production and in vitro effects of the major secondary metabolite produced by Trichoderma species used for the control of grapevine trunk diseases

Abstract: Antibiosis has been shown to be an important mode of action by Trichoderma species used in the protection of grapevine pruning wounds from infection by trunk pathogens. The major active compound from Trichoderma isolates known to protect grapevine pruning wounds from trunk pathogen infection was isolated and identified. The compound, a 6-pentyl-a-pyrone (6PP), was found to be the major secondary metabolite, by quantity, which accumulated in the culture filtrate of T. harzianum isolate T77 and the two T. atrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 33 publications
(43 reference statements)
2
30
0
1
Order By: Relevance
“…After selection of endophytic fungi by the in vitro diffusible metabolite test according to the methodology to Mutawila et al (2015), only one sample was chosen for synergism evaluation. The extract of endophytic fungus was used together with extract of L. sidoides.…”
Section: Synergism Evaluationmentioning
confidence: 99%
“…After selection of endophytic fungi by the in vitro diffusible metabolite test according to the methodology to Mutawila et al (2015), only one sample was chosen for synergism evaluation. The extract of endophytic fungus was used together with extract of L. sidoides.…”
Section: Synergism Evaluationmentioning
confidence: 99%
“…To evaluate the capacity of TaWT, Tr, and Tv of growing using Phi as the P source, we used a modified Vogel's Minimal Medium (VMM) recipe [34], in which the source of P, monopotassium phosphate, was replaced by monopotassium phosphite. VMM is commonly used to cultivate Neurospora crassa, however, it has been also successfully used to grow Trichoderma species including TaWT, Tr, Tv, and T. asperellum [35,36,37,38]. VMM was prepared as a 50X solution and used as a 1X solution and supplemented with glucose 2% and Bacto Agar (DIFCOÔ, USA) 1.5% when needed.…”
Section: Evaluation Of the Capacity Of Trichoderma Wild Type Strains mentioning
confidence: 99%
“…Mutawila et al (2016a) recommend the application of Trichoderma after six hours from the end of sap exudation from cuts and Kotze et al (2011) observed that the use of Trichoderma showed better results than the use of chemicals. Mutawila et al (2016b) found that the 6-pentyl-a-pyrone (6PP) component produced by Trichoderma harzianum and Trichoderma atroviride was shown to inhibit trunk pathogens. In addition, the cleaning of tools is another practice that significantly reduces the infection of plant pathogens in mother plants.…”
Section: Advances Observed In the Management Of New Diseasesmentioning
confidence: 99%